(untitled) (Global Journal of Science Frontier Research, 2020)
The article represents the physical processes and mechanisms that accompany the work of the real p-n-junction in disordered semiconductor structures with deep centers. A model for the transfer of electrons and holes in disordered semiconductors has been developed and expressions for the recombination rate have been obtained, which take into account the exchange of charge carriers between neighboring localized regions. The probability of electronic transitions is calculated. It takes into account the electron-phonon interaction and explains the rapid build-up of reverse currents as the applied voltage increases. The new model of recombination in space charge region of p-n-junction has been developed. This model made it possible to develop a new method for processing current-voltage characteristics and determining the parameters of recombination centers in semiconductor devices including electron-phonon interaction parameters.